Assessment of qualia and affect in urban and natural soundscapes. (September 2021) - Welch, David; Shepherd, Daniel; Dirks, Kim N.; Coad, Gavin; Reddy, Ravi; Tan, Mei Yen; Bhattacharya, Marky
Abstract: The soundscape is unique to each person. It depends on their perception of the sound environment in combination with the traits and states of the person, their memories, and other sensory inputs. In this research, we collected soundscape data from people in large natural environments and combined them with earlier data from city streets to create a dataset that was more varied in sound environment than our previous work. We conducted factor analyses to find patterns in responding, and established a four-factor solution, with factors called: Uplifted, Hectic, Stable, and Demanding. The factors reflected the role of both the perception of the environment (qualia) and the person's internal response (affect) in that Uplifted was based on affective items, Hectic and Stable were based on descriptive items, and Demanding appeared to be based on a combination of affect and qualia. The questionnaire performed well, and validity was supported by differences in the factors across the environments where assessments took place. Feeling Uplifted tended to occur more in natural spaces (parks), as did perceiving the soundscape to be Stable. On the other hand, urban spaces with greater amounts of road traffic were more Hectic and Demanding. Pedestrian areas, dominated by human sounds, fell between the sound environments dominated by nature and traffic sounds. Findings that qualia and affect were both separated and combined in different factors are thought to be consistent with the current understanding of the neural processes in the brain.